Targeted sequencing of mycosis fungoides with large cell transformation. (October 2021) - Wobser, Marion; Roth, Sabine; Appenzeller, Silke; Goebeler, Matthias; Geissinger, Eva; Rosenwald, Andreas; Maurus, Katja
Abstract : Introduction: The presence of large cell transformation (LCT) of mycosis fungoides (MF) has been associated with a higher risk of relapse and progression and consecutively a restricted survival. Up to now, the molecular pathogenesis of LCT is largely unknown. Materials and methods: To address molecular mechanisms of LCT, we performed hybrid capture-based panel sequencing of tissue biopsies of 27 patients (n=10 with LCT versus n=17 without LCT) including follow-up biopsies during the clinical course (51 samples in total). The applied panel included full-length coding regions of 40 lymphoma-associated genes. The analyzed patients were attributed to different groups based on the presence of LCT and clinical behaviour. Results: Our analysis revealed alterations in 27 of the investigated genes with overall 79 protein-altering mutations. Samples of patients with LCT showed the highest mutational load. While in patients with an aggressive behavior a rather heterogenous genetic profile was detected, overlapping genetic aberrations in key signaling pathways and epigenetic modifiers strongly correlated with LCT. If repetitive biopsies were available, some of these genetic aberrations turned out to be of predictive value for successive development of LCT during the subsequent clinical course. Conclusion: We were able to pinpoint convergent molecular alterations as being associated with and/or predictive of LCT in MF. Owing to the adverse prognosis of LCT, this opens the field for more individualized treatment strategies based on the genetic profile. The predictive value of our data set conveys immediate impact for the clinical management: patients with specific genetic alterations might profit from a closer disease monitoring or more aggressive therapies due to their putative higher risk for the development of prognostically adverse LCT during their following disease course.